ANALISIS PEMAHAMAN PENGGUNAAN KONJUNGSI (SETSUZOKUSHI) ~TE KARA DAN ~TA ATODE PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Rizka Nurimanita; Hana Nimashita; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is discuss the comprehension of the use of setsuzokushi ~te kara and ~ta atode by the II, III, IV grade students of Japanese Language Education Study Program University of Riau academic year 2016/2017. The purpose of this research is to measure students ability in using setsuzokushi ~te kara and ~ta atode. Then, to know the difficulty of the use setsuzokushi ~te kara and ~ta atode. This research used quantitative descriptive method by using survey as the research design. The data were obtained by using test and interview the respondents. This research was done as a quantitative research in the field of education. All data processed using statistic method and the result converted by descriptive method to describe the result. Based on the results of the test, it can be seen that the overall level of students' understanding of the use of setsuzokushi ~te kara and ~ta atode is at level D or less, at the interval 40-54,99 with an average of 52.58. The test results show that the highest score is 80 and the lowest score is 30. And highest average score by IV grade students is 55, after that by III grade students is 52. The lowest average score by II grade students is 50,75. The test result also supported by the interview result, respondents are always have a problem in using setsuzokushi ~te kara and ~ta atode. Moreover, based on the interview result respondents are difficult to differentiate between setsuzokushi ~te kara and ~ta atode, and the lack of vocabulary mastery.Keywords : Analysis Understanding, Conjunction (setsuzokushi) ~te kara, Conjunction(setsuzokushi) ~ta atode